Penerapan Teknik Relaksasi Nafas Dalam Pada Pasien Hipertensi Dengan Nyeri Akut - Indah Mamay maftuha; Endah Sari Purbaningsih; Nadia Sindia Devi; Uswatun Khasanah (MEJORA Medical Journal Awatara, 2024)
Hypertension is a condition where there is an increase in blood pressure exceeding 140/90 mmHg cornically. Hypertension is also caused by several factors, one of which is the pattern of consuming salty foods, caffein, consumption of monosodium glutamate (vetsin, soy sauce, shrimp paste).  The method used is a case study approach. The subject in this case study is a patient with a medical diagnosis of hypertension in the Kuta ward of Sumber Kasih Hospital, Cirebon City. The procedure used is providing non-pharmacological deep breathing intervention techniques to hypertensive patients who experience acute pain. The deep breathing relaxation technique is carried out with a frequency of 15 times for approximately 10 – 15 minutes. Repeat if the patient feels pain. On the first day the patient still complained of pain but on the second day the pain began to decrease and on the third day the pain began to disappear. The patient also said that if the head hurts, the patient does deep breathing relaxation techniques and this reduces the pain quite a bit. From the results of the nursing care that has been provided and the interventions that have been carried out, it can be concluded that the deep breathing relaxation technique is effective in reducing pain. These non-pharmacological techniques can be used as companions to pharmacological therapy.